TRADE-OFF INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN - Marihot Nasution; Hafidz Huzaifah (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
This study examined the Phillips curve theory and Okun's Law in Indonesia, whether there is an agreement on two theories to the real conditions that occur in the field. Some previous studies found that unemployment has a unidirectional relationship with inflation where it is not in line with the Phillips curve theory. Similarly, the relationship between economic growth and unemployment. Earlier studies suggested that in the short term, there is a negative relationship between unemployment and economic growth. This condition is not in accordance with Okun's law. The purpose of this study was to determine the relationship between inflation, economic growth and the unemployment rate. The study will be conducted using the Granger Causality Test to look at the causal relationships between variables.